Behaviour of Evapotranspiration Evaporation Ratio and Leaf Area Index During Different Phenophase of Kharif Groundnut (ARACHIS Hypogaea L.) - Patel, K I; Mehta, A N; Shekh, A M; Dhotre, A K (Annals of Arid Zone, 2016)
The evapotranspiration rate and the corresponding ratio of evapolranspiration to evaporation during various phenological stages of the kharif groundnut (Arachis hypogaea L. Cv. JL-24) were studied during 1986 to 1988. The ET/E during 1986,1987 and 1988 reached the peak values of 2.0, 1.79 and 1.36, respectively during peg formation stage of the crop and were established earlier than the leaf area index (LA!) attained during the pod formation stage of crop. The highest values of LA! observed during the year 1986, 1987 and 1988 were 9.3, 10.0 and 7.5, respectively. During flowering stage (up to 30 DAS) ET/E was found higher in 1988 than 1986 and 1987. Bul later on (from 30 to 65 DAS) ET/E was found progressively higher in 1986 and 1987 than 1988. During peg formation to pod development stage (from 65 to 90 DAS) of the crop, the ET/E was found higher in 1987 than 1986 and 1988, which had the, highest pod yield.